Sustainable shipping: a critical review for a unified framework and future research agenda - Zhou, Yusheng (2023)
With the development of the global economy and shipping industry, sustainable shipping has attracted the attention of both the industry and academia. However, the concept of sustainable shipping remains ambiguous. This paper investigates the motives, drivers, and benefits of sustainable shipping, as well as the critical success factors, antecedents, barriers and solutions. Moreover, this review contributes to the literature by zooming in on the concepts of sustainable shipping management and synthesising its scattered dimensions by introducing a unified framework, comprising environmental, social, and economic pillars. The differences between sustainable shipping and environmental shipping have also been highlighted. Future research directions in the field of sustainable shipping are also recommended from four perspectives, namely the interrelationship between environmental and social pillars, investment strategies in sustainable shipping, risk assessment of sustainable shipping, and post pandemic sustainable shipping.